Reliability-based importance assessment of structural members with applications to complex structures - Onoufriou, Toula; Gharaibeh, Emhaidy S.; Frangopol, D.M. (My University, 2002)
In dealing with ranking structural members and identifying critical components in any structural system, different aspects should be considered to quantify the importance of all components and to rank them in a proper order. These aspects include but are not limited to: location of each individual component in the system, safety level of each member, stiffness sharing of each member, and material behavior of each member. For simple structures this task may be trivial and straight forward. For complex structures idealized by mixed series-parallel arrangements, however, this task gets complex and it should be addressed on a system performance perspective and not on individual component checks. This study presents a reliability-based methodology to identify and rank important members in structural systems under different material behaviors and for different stiffness sharing factors. The results presented can be used to develop a rational methodology for prediction of critical members in structural systems. The approach takes into consideration system performance as a whole instead of dealing with individual members and quantifies the impact of each individual component on the performance of the system. Two types of member importance factors, proposed by the first and second authors, are formulated in this study: member reliability importance factor, which measures the sensitivity of system reliability to changes in member reliability level, and member post-failure importance factor, which measures the sensitivity of system reliability to changes in member post-failure behavior. These factors can be used to better predict the reliability and post-failure importance of structural members in complex systems such as highway bridges and offshore platforms. A discussion, provided by the third author, on system effects in two offshore structures is also presented.
Keywords: Reliability; Maintenance; Structural Systems Research Project